Type 2 diabetes mellitus patients, profile, achievement and complications in primary health care in Surabaya, Indonesia - Linda Dewanti; Mark A. Graber; - Sulistiawati; - Atika; Adikara P. Pratama; Tan N. Octora; Dyah A. Prajnaparamitha; Raudia F. Humaidy (Population Medicine)
Introduction The prevalence of type 2 diabetes mellitus (T2DM) continues to increase worldwide. Indonesia is no exception. The diagnoses of prediabetes and diabetes are increasing and seen in ever younger patients. Primary Health Care (PHC) plays a pivotal role in managing this disease in the community. This study aimed to determine the achievement therapy of T2DM patients in a PHC center in Surabaya, the second most populous city in Indonesia.